Serum levels of LH, FSH, estradiol and progesterone in female rats experimentally infected by Trypanosoma evansi - Faccio L. (2013)
The goal of this study was to evaluate reproductive hormones in sera samples of female rats experimentally infected by Trypanosoma evansi during different phases of the estrous cycle. For that, 64 animals were divided into two groups: 24 rats for the control group (uninfected), and 40 animals were infected by T. evansi. These groups were divided into subgroups according to the time of infection (days 5 and 15 post-infection; PI) and the phase of the estrous cycle (proestrus, estrus, metestrus and diestrus). Serum was collected at days 5 and 15 PI and the levels of luteinizing hormone (LH), follicle stimulating hormone (FSH), progesterone and estradiol were assessed by enzyme immunoassay technique. The concentration of nitrite/nitrate (NO. x), advanced oxidation protein products (AOPP), and thiobarbituric acid reactive substances (TBARS) were measured in ovaries and uteruses in these same periods. Infected females showed significant decrease (P<. 0.05) of LH, FSH, estradiol and progesterone in different periods and phases of the estrous cycle when compared to uninfected rats. In addition, it was observed an increase in the concentration of NO. x, AOPP, and TBARS in the ovaries, which is indicative of cell damage. Therefore, our experimental study showed that T. evansi infection in female rats may cause changes in LH, FSH, estradiol, and progesterone levels regardless of the time of infection or phase of the estrous cycle. © 2013 Elsevier Inc.